Abu Shouk, Ahmad. “Islamic Interpretation of History: Rationale, Paradigms, and Methodological Problems,” Year 10, Issues 37-38 (Summer-Fall 1425 AH/ 2004 CE), Pp. 129-154. - أبو شوك أحمد ابراهيم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2004)
Ahmad Abu Shouk discusses the intellectual rationale of a set of assumptions that led to the emergence of Islamic interpretation of history in the latter half of the last century, and analyzes the Islamic modules presented in this regard as substitutes for Western modules that deal with the interpretation of history. He then reviews the methodological problems that face these modules and means of correcting them. His study finds that the Islamic interpretation of history stands on a solid foundation, which is better than the Western secular foundation of interpretation; however, it is unable to employ intellectual theories prevailing in the other civilizations in a positive way in its general Islamic framework.